Promoting Decent Employment in Agriculture and Food Sectors of Developing Countries: What Role for CGIAR? - Balié, Jean; Clayton, Andrew (CGIAR System Organization, 2024)
One of CGIAR’s five core impact areas is poverty reduction, livelihoods, and jobs. Our ambition needs to go beyond creating jobs and generate higher income for farmers. We must also look at the quality of the jobs and livelihoods created through agricultural transformation. This is about providing decent work in rural economies that respect fundamental labor rights and gender equality and provide fair wages and basic social protection. We think that this has not been given sufficient attention in CGIAR’s research portfolio. In this blog, we set out why promoting decent employment in the agriculture and food sectors of developing countries should prioritized within CGIAR.